Giant magnetoelectricity in soft materials using hard magnetic soft materials. (February 2023) - Rahmati, Amir Hossein; Jia, Rong; Tan, Kai; Liu, Liping; Zhao, Xuanhe; Deng, Qian; Sharma, Pradeep
Abstract: Imagine a material that will produce electricity via a contactless, wireless signal. Further, we hope that this material is capable of large deformation reminiscent of soft robots and is soft enough to conform to irregular or curved geometries. This would all be possible if soft magnetoelectric materials were available; paving the way for applications such as remote drug delivery, energy harvesting, soft robots, multiple state memories among others. Here, for the first time, using the concept of hard magnetic soft matter in combination with electrets, we design and create a soft magnetoelectric material that exhibits an extremely strong, self-biased magnetoelectric effect. Further, using programmable pattern of deposition of magnetic dipoles and charges, we report a giant magnetoelectric coefficient in an ultra-soft deformable material that retains its strength even under infinitesimal external fields and at low frequencies. Highlights: A magnetoelectric (ME) material is capable of converting a magnetic field into electricity and vice versa. Soft robots, wireless energy harvesting, drug delivery via remote action, multiple state memories are just some of the possible applications of this phenomenon. The magnetoelectric property is however rare and restricted either to certain hard exotic crystals that satisfy a stringent set of material symmetry constraints or painstakingly fabricated (still hard) composites. Soft ME materials capable of large deformations do not exist. In this paper, for the first time, we introduce a novel class of soft ME materials with a giant self-biased magnetoelectric effect. We design and fabricate bio- compatible ME materials capable of large deformation and that are soft enough to conform to irregular geometries.